Culture moderates children's responses to ostracism situations. [article]. - Over, Harriet
Across a series of studies, we investigated cultural differences in children's responses to ostracism situations. Working with the children of farmers and herders, we focused on how painful children estimate ostracism to be. Study 1a showed that 4- to 8-year-old children from a socially interdependent farming community estimated ostracism to be less painful than did children from an independent herding community. Study 1b showed that this cultural difference was specific to social pain and did not apply to physical pain. Study 2 replicated the results of Study 1a and showed that individual differences in parents' level of social interdependence mediated the relationship between cultural group and how painful children estimate ostracism to be. Study 3 replicated this effect again and showed that children's tendency to recommend seeking social support following ostracism mediated the relationship between cultural group and the perceived pain of being excluded. Finally, Study 4 investigated cultural differences in moral responses to ostracism and showed that children from the farming community punished an individual who ostracized someone else less harshly than did children from the independent herding community. Thus different economic cultures are associated with striking differences in social interdependence and responses to ostracism from early in development. -- (from the authors)
Keywords: Uskul, Ayse K; Ostracism; Social-cognitive development; Herders and farmers; Interdependence; Turkey